2009
DOI: 10.1159/000200809
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Dermatolysis, Tissue Necrosis and Impaired Wound Healing due to Sunitinib Treatment Leading to Forefoot Amputation

Abstract: Innovative treatment strategies in urologic oncology confront the treating physician with a new spectrum of adverse events. With growing understanding of underlying pathomechanisms, we need to identify contraindications against the use of certain antiproliferative drugs. The management of toxicities involves a multidisciplinary approach and thus, the exchange of experience across medical specialties is mandatory. We report a case of fulminant toxic dermatolysis, tissue necrosis and impaired wound healing resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Moreover, it has been suggested that underlying microangiopathy and neuropathy may act as precipitating factor for erosions/ulcers (3). This hypothesis is supported by our case and others (4,6). These cases all involved patients with type II diabetes, leading us to speculate that pre-existing diabetic microangiopathy may have played a role in the observed reactions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, it has been suggested that underlying microangiopathy and neuropathy may act as precipitating factor for erosions/ulcers (3). This hypothesis is supported by our case and others (4,6). These cases all involved patients with type II diabetes, leading us to speculate that pre-existing diabetic microangiopathy may have played a role in the observed reactions.…”
Section: Discussionsupporting
confidence: 92%
“…We confirm the lack of a clear dose relationship as our patient relapsed at a half-dose. In two previous cases (3,4), skin necrosis of the extremities could be considered a severe variant of hand-and-foot skin reaction. The present case bears similar features, with our patient simultaneously developing handand-foot skin reaction and skin ulcers.…”
Section: Discussionmentioning
confidence: 98%
“…Delayed pneumocephalus after VPS placement is unusual and seems to be associated with a skull base defect. We propose that in our patient air could gain access to retropharyngeal spaces via the dental defect secondary to tooth extraction, a process which may be favored by delayed healing secondary to sunitinib as previously described [3,4], and follows the VPS to provoke pneumocephalus as suggested by the presence of air in the neck beside the VPS. Afterwards, the pressurized pneumocephalus could drain into the peritoneum via the oneway flow control valve, permitting more and more air to go through the VPS with the increasing pressure in the cerebral ventricles.…”
mentioning
confidence: 55%
“…One case report described a patient who experienced tissue necrosis, fulminant toxic dermatolysis and impaired wound healing resulting in the amputation of the forefoot, following 6 days of treatment with sunitinib 20 . The patient had been taking 50 mg of sunitinib daily for 6 days, then presented with swelling, erythema and blisters on the right foot 20 . Subsequent necrosis of the foot occurred resulting in amputation.…”
Section: Agents Targeting Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%